A política de ressocialização no Brasil: Instrumento de Reintegração ou de Exclusão Social? - Santiago, Glaydson Alves da Silva (2011)
The present study it has for objective to analyze the actions of the politics of ressocialização of the prisoners in Brazil, being had as main instrument of analysis the Law of Criminal Executions - LEP, promulgated in 1984, where if it defends that, even so private of freedom, the excessively right inmates keep the title of basic ones, having the execution to occur of form to facilitate to its reintegration in the society, preparing its reinserção in responsible way. For in such a way, we carry through a historical rescue of the phenomenon of the arrest and the penalties, while construction social human being and, detaching the Brazilian context of the arrests and having the pernambucano prisional system, especially, the Penitentiary Teacher Aníbal Bruno - PPAB, situated in Recife, as lócus of inquiry. In this perspective, we adopt the bibliographical survey, the documentary analysis and the research of field as the main metodológicos resources for approach of the reality and, during the field research, the comment and the interview with egresses of the prisional system, had been elect the main instruments for collection of data. Of ownership of these data, we submit the same ones to an analysis based on six constructed theoretical categories from the assistance foreseen in the proper Law of Criminal Executions, that is, material, educational assistance, to the health, legal, social and religious. These categories had guided our analyses and had been compared with the stories presented for the interviewed egresses and data consolidated of the system of information of the Ministry of Justice. The results demonstrate that the actions foreseen in the LEP are not accomplished in the reality of the PPAB, and that such fact if extends to the Brazilian penitentiaries, in general way. E, discloses, still, that the possibilities of ressocialização of the prisoners inexist in these environments, where if strengthens the exclusion of these individuals already kept out of society by the system, therefore it does not guarantee attendance to the basic necessities of survival and dignity human being. In this perspective, we defend the construction of one politics that sees the system penitentiary as an effective space of citizenship construction; that it considers the basic rights of the citizens and searchs the ways for the rescue of the lost dignity in the years of jail.